The aesthetics of the formal relationship between visual arts and cyber architecture (Al-Academy, 2025)
This research aims to uncover the aesthetics of the formal relationship between visual arts and cyber architecture. To achieve this, a descriptive-analytical approach was employed, examining the aesthetics of the formal relationship between visual arts and cyber architecture. A content analysis approach was also used to analyze selected artworks found on websites. A purposive sample of three artworks was selected based on their compatibility with the topic and scope of the current research, as well as the diversity of their artistic techniques and styles. The research results showed that the shared aesthetics between visual arts and cyber architecture draw the viewer's attention to the intersection between them, which creates comfort and appeal, and achieves integration and innovation in a new style for aesthetic concepts. Visual arts also relies on many formal relationships associated with cyber architecture, such as flexibility, fluidity, and abstraction. Cyber ​​architecture has also paved the way for the visual arts to create spaces for intelligent and interactive systems, enabling them to achieve unprecedented aesthetic expressions that redefine the relationship between humans, art, and technology. The research recommends conducting further studies on the aesthetics of cyber architecture and its impact on the artistic field, and holding diverse art exhibitions that combine art and architecture by showcasing interactive experiences. It also recommends enhancing communication between artistic, architectural, and technological disciplines, opening new horizons for development and co-creation.